The evaluation of serviceability of internal combustion engine with diagnostic criteria for testing modified pistons in laboratory conditions - P. V. Litvinov; V. R. Vedruchenko; V. A. Borisov; A. V. Shtib (Омский научный вестник)
Diagnostic practice shows that the design of an engine and its systems is complicated in order to improve its environmental safety. In this case, the diagnostics and tests necessary in this case, often, can’t be carried out on an automobile engine in conditions of its actual operation. This includes the testing of pistons modified with catalytic coatings. The conditions of their testing and the criteria for diagnosis and performance are discussed in this article.